A regional satrap, a Hindu nationalist and a conservative congressman: Dwarka Prasad Mishra (1901–1988). Issue 1 (2nd January 2016) - Ankit, Rakesh
Abstract : DP Mishra, chief minister of Madhya Pradesh from 1963 to 1967 and twice minister in Central Provinces and Berar (1937–1939, 1946–1950), was a key figure in Congress politics and provincial governance from the pre- to the post-independence period in India. Mishra was a noted Patel acolyte and a vocal critic of Nehru. A Brahmin leader, he identified with an elite-based Hindu politics of caste and community. He was also an efficient administrator and his career peaked in 1966–1967 when he acted as a counsellor to Prime Minister Indira Gandhi. In this paper, I argue that his political life is an important prism through which to view Congress politics, its High Command culture, its character in provinces/states and its continuities with the colonial state in governance.